Perspektywiczne kierunki rozwoju biologii człowieka w Polsce, ze szczególnym uwzględnieniem auksologii - Napoleon Wolański; Anna Siniarska (Studia Ecologiae et Bioethicae)
Protoculture has already existed in animals and is manifested by using a natural object as a tool or by coping the habits of another animals being successful in doing something. At the beginning it was the practice of everyday life, the act of survival, what can be understood as “technique”. After that the process of rational cognition (theory) takes place, and innovative theories propagate the “science” development. Science discovers rules in our nature and society as well as in human activity called culture. Science is a certain sphere of consciousness including self-consciousness, thus science could be created together with consciousness, as a product of thinking mind. Such mind is possessed by humans only.